Insect attachment on crystalline bioinspired wax surfaces formed by alkanes of varying chain lengths - Gorb, Elena; Böhm, Sandro; Jacky, Nadine; Maier, Louis-Philippe; Dening, Kirstin; Pechook, Sasha; Pokroy, Boaz; Gorb, Stanislav (Beilstein Journal of Nanotechnology, 2014)
The impeding effect of plant surfaces covered with three-dimensional wax on attachment and locomotion of insects has been shown previously in numerous experimental studies. The aim of this study was to examine the effect of different parameters of crystalline wax coverage on insect attachment. We performed traction experiments with the beetle Coccinella septempunctata and pull-off force measurements with artificial adhesive systems (tacky polydimethylsiloxane semi-spheres) on bioinspired wax surfaces formed by four alkanes of varying chain lengths (C36H74, C40H82, C44H90, and C50H102). All these highly hydrophobic coatings were composed of crystals having similar morphologies but differing in size and distribution/density, and exhibited different surface roughness. The crystal size (length and thickness) decreased with an increase of the chain length of the alkanes that formed these surfaces, whereas the density of the wax coverage, as well as the surface roughness, showed an opposite relationship. Traction tests demonstrated a significant, up to 30 fold, reduction of insect attachment forces on the wax surfaces when compared with the reference glass sample. Attachment of the beetles to the wax substrates probably relied solely on the performance of adhesive pads. We found no influence of the wax coatings on the subsequent attachment ability of beetles. The obtained data are explained by the reduction of the real contact between the setal tips of the insect adhesive pads and the wax surfaces due to the micro- and nanoscopic roughness introduced by wax crystals. Experiments with polydimethylsiloxane semi-spheres showed much higher forces on wax samples when compared to insect attachment forces measured on these surfaces. We explain these results by the differences in material properties between polydimethylsiloxane probes and tenent setae of C. septempunctata beetles. Among wax surfaces, force experiments showed stronger insect attachment and higher pull-off forces of polydimethylsiloxane probes on wax surfaces having a higher density of wax coverage, created by smaller crystals.
Keywords: Coccinella septempunctata; insect–plant interactions; plant waxes; pull-off force; traction force